Directional shear flow and Rho activation prevent the endothelial cell apoptosis induced by micropatterned anisotropic geometry - Wu, Chia-Ching (National Academy of Sciences, 2007)
To study the roles of anisotropic cell morphology and directionality of mechanical force in apoptosis, the spreading of human umbilical vein endothelial cells (HUVECs) was constrained by growing on micropatterned (MP) strips of fibronectin (FN, 20 μg/cm(2)) with widths of 15, 30, and 60 μm on silicone membrane. Cells on 30- and 60-μm strips, like cells on a nonpatterned (NP) surface coated with FN, showed clear actin stress fibers with anchoring spots of phosphorylated focal adhesion kinase (p-FAK) and no significant apoptosis. On 15-μm strips, cells had few stress fibers, no p-FAK, and significant apoptosis. After seeding for 12 h, the cells were subjected to pulsatile shear stress (12 ± 4 dyn/cm(2)) parallel or perpendicular to MP strips, or kept under static condition. Parallel flow caused cell elongation with enhanced stress fibers and p-FAK, and a reduction in apoptosis, but perpendicular flow did not. The Rho inhibitory C3 exoenzyme abolished the effects of parallel flow. RhoV14, the constitutively active Rho, enhanced stress fibers and p-FAK, and prevented apoptosis of HUVECs on 15-μm strips under static condition. RhoV14 also reduced cell apoptosis under both parallel and perpendicular flows. Our results indicate that cell apoptosis can be modulated by changes in ECM micropatterning, anisotropic cell morphology, and mechanical forces. These extracellular microenvironment factors affect cell survival through alterations in Rho GTPase activity, stress fiber organization, and FAK phosphorylation.